DESIGNING A GAME-BASED LEARNING IN PHYSICS EDUCATION USING AUGMENTED REALITY - Siti Feirusz Ahmad Fesol; Marsya Dayana Salehuddin (Journal of Islamic, Social, Economics and Development, 2022)
Physics education is considered the most complicated subject in school and served as the basis for modern technology and tools used for research and development in science, engineering, and healthcare. However, from the survey that has been conducted among the science stream students, there are two (2) issues that have been identified which are the students think that learning Physics is difficult to understand (agreed by 73%) and learning physics using textbooks only is less enjoyable (agreed by 62%). To solve these, this study aims to propose a model for designing Physics education applications using the game-based learning approach to create a more enjoyable learning environment with the assistance of the Augmented Reality (AR) element. This application employs the Rapid Application Development (RAD) methodology. The proposed solution was tested using a usability testing strategy to assess the system usability while learning Physic through game-based learning using Augmented Reality (AR) for science stream students. The results of the study revealed that the designed system received an average score of 71.83% which indicates that the system has good, strong system usability in terms of its effectiveness, efficiency, and satisfaction of the respondents when using the proposed application in learning Physics. In the future, the proposed model can also be implemented in developing other subjects.